How much do we care about teacher job insecurity during the pandemic? A bibliometric review - Gómez-Domínguez, Valentina; Navarro-Mateu, Diego; Gómez-Domínguez, Teresa; Giménez-Espert, María del Carmen (Frontiers in Public Health, 2023)
In this study, a descriptive bibliometric analysis of the scientific production in the Web of Science on job insecurity perceived by teachers in pandemic situations was carried out. The result shows the growing interest in the topic with an upward trend with an annual growth of 41.52%. Forty-seven papers from 41 journals with 2,182 cited references were considered, with 149 researchers from 30 countries publishing at least one article. The country with the most publications was the United States, followed by Germany and Spain. The United States was the country with the most collaborations. A total of 95 institutions published papers, and the universities with the most registrations were Miami University and the University of the Basque Country, although York University and the University of the Basque Country had a higher overall citation coefficient (102 and 40, respectively). Of the 41 journals that have published on the topic, Frontiers in Education and the British Journal of Educational Psychology stood out in terms of their article numbers. However, this last one was superior in terms of the overall number of citations per year, followed by Frontiers of Psychology.